Geochemistry of mafic Paleocene volcanic rocks in the Valle del Cura region: Implications for the petrogenesis of primary mantle-derived melts over the Pampean flat-slab - Litvak, Vanesa Dafne (2010)
Mafic volcanism of Paleocene age was recently reported in the Valle del Cura region and the El Indio Belt in the aphanitic and very homogenous well-preserved lavas flows of the Río Frío Basalts unit. These are high-K basalts, with high Fe2O3 and TiO2 contents that imply an alkaline tendency and show typical intraplate-type patterns on a MORB normalized trace elements plot. Sr and Nd isotopic ratios evidence a mantle affinity. The chemistry indicates that these rocks are high temperature melts that result from a low degree of melting of an enriched portion of lithospheric mantle, with no contamination from crustal derived components. The alkaline back-arc Las Máquinas Basalts of Lower Miocene age are derived from more primitive magmas closer to the original source. Mantle composition was relatively constant from Paleocene to Lower Miocene in the studied latitudes over the Pampean flat-slab. Both mafic units share the isotopic trend of pre-Miocene mafic lavas from the Central Andes that were not affected by crustal contamination. Post-Miocene mafic lavas show a strong influence from crust-related processes.